Cardiac arrhythmia induced by genetic silencing of ‘funny’ (f) channels is rescued by GIRK4 inactivation - Mesirca, Pietro; Alig, Jacqueline; Torrente, Angelo G.; Müller, Jana Christina; Marger, Laurine; Rollin, Anne; Marquilly, Claire; Vincent, Anne; Dubel, Stefan; Bidaud, Isabelle; Fernandez, Anne; Seniuk, Anika; et al. (Nature communications, 2014)
The mechanisms underlying cardiac automaticity are still incompletely understood and controversial. Here we report the complete conditional and time-controlled silencing of the ‘funny’ current ( I f ) by expression of a dominant-negative, non-conductive HCN4-channel subunit (hHCN4-AYA). Heart-specific I f silencing caused altered [Ca 2+ ] i release and Ca 2+ handling in the sinoatrial node, impaired pacemaker activity and symptoms reminiscent of severe human disease of pacemaking. The effects of I f silencing critically depended on the activity of the autonomic nervous system. We were able to rescue the failure of impulse generation and conduction by additional genetic deletion of cardiac muscarinic G-protein-activated (GIRK4) channels in I f -deficient mice without impairing heartbeat regulation. Our study establishes the role of f -channels in cardiac automaticity and indicates that arrhythmia related to HCN loss-of-function may be managed by pharmacological or genetic inhibition of GIRK4 channels, thus offering a new therapeutic strategy for the treatment of heart rhythm diseases. The ‘funny’ current ( I f ) is important for the generation and regulation of the heart’s automaticity. Here the authors show that I f silencing through genetic modification of the f -channel component HCN4 causes heart arrhythmia by altering Ca 2+ handling in pacemaker myocytes.